B308 Select the new onq silver soaker catheter versus the thoracic epidural, the ancient golden standard in eras colorectal surgery: a prospective superiority cohort study. (11th August 2022) - Abusaris, CA; van Vugt, ST; Bleeker, WA; Ott, A
Abstract : Background and Aims: The aim of this study was to compare ropivacaine-loaded catheters (intra-abdominal and preperitoneal) with the former golden standard of ERAS guidelines, the thoracic epidural anesthesia (TEA) in postoperative pain management after laparoscopic colorectal surgery. Methods: This prospective cohort study included 48 patients eligible for colorectal surgery between July 2018 and November 2019. 25 patients received a TEA with ropivacaine/sufentanil (cohort 1), 23 received an intraoperative i.v. lidocaine infusion and 2 catheters at the end of surgery (cohort 2).The Regional Ethics Committee Leeuwarden, The Netherlands gave ethical approval.The primary outcome was length of stay (LOS). Opioid consumption, NRS pain scores, time in the PACU and mobilization into a chair, catheter dislocation, development of prolonged ileus, need for urinary catheter and patient satisfaction were also assessed. Results: We observed a median LOS of 5 days in cohort 1 and 4 days in cohort 2 (p = 0.07 ). Applying a 5 day cut-off, cohort 2 yielded more patients with a LOS < 5 days (p< 0.001 ). In cohort 1 all patients needed a urinary catheter, in cohort 2 there were 2 (p < 0.001 ). The postoperative opiate consumption didn't show significant differences; the intraoperative dose was significantly higher in cohort 2 patients (p< 0.001 ) Other secondary outcomes didn't differ statistically. Conclusions: We showed tendency to shorter LOS with comparable pain scores.This study demonstrates that the analgesic quality of peripheral nerve block catheters in the abdominal wall and preperitoneal is equal to a thoracic epidural.